2017
DOI: 10.1259/bjr.20170290
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying potential reduction in contrast dose with monoenergetic images synthesized from dual-layer detector spectral CT

Abstract: 50 keV monoenergetic images provided the best balance of improved CNR on all studies (mean 2.4-fold increase in vivo) for enhancing vessels vs image noise. A 50% reduction in contrast dose on a 50 keV image should maintain comparable or better CNR as compared with polychromatic CT in over 80% of CT studies. Advances in knowledge: Use of a novel, single-source, dual-layer detector spectral CT scanner to improve visualization of contrast-enhanced blood vessels will reduce the amount of iodinated contrast require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…On the other hand, dual-layer spectral detector CT enables the simultaneous collection of low- and high-energy data, and the imaging data acquired from dual-layer spectral detector CT can be reconstructed to virtual monochromatic images with photon energy levels of 40-200 keV by on-demand and immediate retrospective spectral analysis. Previous reports showed that CT attenuation and CNR had increased as the X-ray energy of virtual monochromatic images was decreased [6] , [12] . A past report revealed that 50-keV images achieved the same CNR of a 120-kVp image with a 2.5-fold reduction in iodine concentration and 40-keV virtual monochromatic images achieved the same CNR of a 120-kVp image with a 4.0-fold reduction in iodine concentration [6] .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, dual-layer spectral detector CT enables the simultaneous collection of low- and high-energy data, and the imaging data acquired from dual-layer spectral detector CT can be reconstructed to virtual monochromatic images with photon energy levels of 40-200 keV by on-demand and immediate retrospective spectral analysis. Previous reports showed that CT attenuation and CNR had increased as the X-ray energy of virtual monochromatic images was decreased [6] , [12] . A past report revealed that 50-keV images achieved the same CNR of a 120-kVp image with a 2.5-fold reduction in iodine concentration and 40-keV virtual monochromatic images achieved the same CNR of a 120-kVp image with a 4.0-fold reduction in iodine concentration [6] .…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports showed that CT attenuation and CNR had increased as the X-ray energy of virtual monochromatic images was decreased [6] , [12] . A past report revealed that 50-keV images achieved the same CNR of a 120-kVp image with a 2.5-fold reduction in iodine concentration and 40-keV virtual monochromatic images achieved the same CNR of a 120-kVp image with a 4.0-fold reduction in iodine concentration [6] . Thus, adequate images for diagnosis can be obtained by dual-layer spectral detector CT even if the amount of contrast media is reduced.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Research have shown that spectral imaging can improve the visibility of contrast-enhanced blood vessels, thereby reduce the required amount of iodinated CM. 14,15 To the best of our knowledge, no correlative study is yet available on "double low" hepatic DEsCT. The present study evaluated the effect of ASIS and adaptive statistical iterative reconstruction (ASiR) algorithm technique in the reduction of radiation and CM dose in typical hepatic hemangioma (HH) DEsCT.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a contrast media reduction method using virtual monochromatic X-ray imaging by dual energy CT has been reported [189][190][191][192][193][194] in which virtual monochromatic X-ray images are generated based on dual energy data and it is possible to virtually represent a CT image of an arbitrary single energy level [effective energy (keV)]. The lower the single energy, the higher the CT value of the iodine contrast media.…”
Section: Level Of Evidence: Iva/grade Of Recommendation: C1 (Minds 2017) Quality Of Evidence: C/strength Of Recommendation: 2 Rationale Cmentioning
confidence: 99%